Urinary TIMP2 and IGFBP7 Identifies High Risk Patients of Short-Term Progression from Mild and Moderate to Severe Acute Kidney Injury during Septic Shock: A Prospective Cohort Study. (1st April 2019) - Maizel, Julien; Daubin, Delphine; Vong, Ly Van; Titeca-Beauport, Dimitri; Wetzstein, Morgane; Kontar, Loay; Slama, Michel; Klouche, Kada; Vinsonneau, Christophe
Abstract : Background . To examine whether the new urinary biomarkers TIMP2 and IGFBP7 can predict progression within 24 hours and 72 hours from mild and moderate (KDIGO 1 or 2) to severe (KDIGO 3) AKI in patients with septic shock. Methods . A prospective, multicenter observational study performed in three French ICUs. The urinary biomarkers TIMP2∗ IGFBP7 were analyzed at the early phase (<6 hours) of patients admitted for septic shock with mild and moderate AKI. Results . Among the 112 patients included, 45 (40%) progressed to the KDIGO 3 level 24 hours after inclusion (KDIGO 3 H24) and 47 (42%) 72 hours after inclusion (KDIGO 3 H72). The median urinary TIMP2∗ IGFBP7 at inclusion (baseline) were higher in the KDIGO 3 group than in the KDIGO<3 group at H24 and H72. All covariates with ap value < 0.1 in the univariate analysis were included in stepwise multiple logistic regression models to identify factors independently associated with the risk of KDIGO 3 at H24 and H72. TIMP2∗ IGFBP7 remained independently associated with KDIGO 3 at H24 and H72. Baseline posology of norepinephrine, baseline urine output, and baseline serum creatinine remained also significantly associated with progression to KDIGO 3 at H24. Baseline TIMP2∗ IGFBP7 and baseline urinary output had the best AUC ROC. A baseline TIMP2∗ IGFBP 7 > 2.0 (ng/ml) 2 /1, 000 identified the population at high risk of KDIGO 3 H24 (relative risk 4.19 (1.7-10.4)) with a sensitivity of 76% (60-87) and a specificity of 81% (69-89). But the diagnostic performance at H72 of baseline TIMP2∗ IGFBP7 was poor (AUC: 0.69 (0.59-0.77)). Conclusion . The urinary TIMP2∗ IGFBP7 concentration and the urine output at the early phase of septic shock are independent factors to identify the population at high risk of progression from mild and moderate to severe AKI over the next 24 but not 72 hours. A TIMP2∗ IGFBP7concentration > 2.0 (ng/ml) 2 /1, 000 quadruples the risk of KDIGO 3 AKI within 24 hours. This trial is registered with (NCT03547414 ).